Survival Of The Major Character In Daphne Du Maurier's Rebecca: An Individual Psychological Perspective - Fitriansyah, Septiana, Drs. Abdillah Nugroho, M. Hum, Nur Hidayat, M.Pd (2014)
The study is an individual psychological analysis on Daphne du Maurier'sRebecca. This study focuses on how Alfred Adler's principles of individual psychology theory are reflected in Mrs. de Winter's characters at the late of nineteenth century. The research aims at analyzing Daphne du Maurier' Rebecca from Individual Psychological perspective. This theory states basically the activities of human's life are motivated by two principles of motivation, striving for superiority and social interest. In conducting the study, the researcher uses the theory of Individual Psychological perspective. The theory of Individual psychological perspective is appropriate because the theory includes six principles of human's personality systems, inferiority feeling and compensation, striving for superiority, fictional finalism, creative self, social interest and style of life and its conflicts resulted from them. While the novel itself deals with the struggle of young woman from lower class who is inexperienced in life to fight for her acknowledgement in her environment. The outcome of the study shows the following conclusions. First, based on structural analysis, it is clear that through the novel, the writer of the novel wants to illustrate how a woman has to fight for her acknowledgement through her roles in a family and society. Second, based on the psychological analysis, Daphne du Maurier'sRebecca tells about the survival of Mrs. de Winter in order to fight for her existence in the society.